2015
DOI: 10.1002/jae.2430
|View full text |Cite
|
Sign up to set email alerts
|

The Measurement and Behavior of Uncertainty: Evidence from the ECB Survey of Professional Forecasters

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
76
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(78 citation statements)
references
References 39 publications
1
76
0
1
Order By: Relevance
“…Several different methods have been used to measure uncertainty based on the reported density (histogram) forecasts. In some cases, the uncertainty measure is derived from the individual density forecasts assuming that the probability mass within each interval is concentrated at the midpoint of each interval [Rich and Tracy (2010), Kenny et al (2015)], or that the probability mass is distributed uniformly within each interval [Zarnowitz and Lambros (1987), Abel et al (2016)]. 2 In other cases, the uncertainty measure is derived by fitting a continuous distribution to the individual density forecasts, where the continuous distribution is a normal distribution [Giordani and Soderlind (2003), Boero et al (2014)], a generalized beta distribution [Bruine de Bruin et al (2011)], or both [Clements (2014a[Clements ( , 2014b].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Several different methods have been used to measure uncertainty based on the reported density (histogram) forecasts. In some cases, the uncertainty measure is derived from the individual density forecasts assuming that the probability mass within each interval is concentrated at the midpoint of each interval [Rich and Tracy (2010), Kenny et al (2015)], or that the probability mass is distributed uniformly within each interval [Zarnowitz and Lambros (1987), Abel et al (2016)]. 2 In other cases, the uncertainty measure is derived by fitting a continuous distribution to the individual density forecasts, where the continuous distribution is a normal distribution [Giordani and Soderlind (2003), Boero et al (2014)], a generalized beta distribution [Bruine de Bruin et al (2011)], or both [Clements (2014a[Clements ( , 2014b].…”
Section: Literature Reviewmentioning
confidence: 99%
“…5 Examining matched point and density forecasts, Rich and Tracy (2010) find a very weak relationship between disagreement and uncertainty for the US-SPF. Recent analyses that have examined data from other surveys featuring point and density forecasts, such as Boero et al (2008) for the BOE-SEF and Abel et al (2016) for the ECB-SPF, have found little support for the use of disagreement as proxy for uncertainty. 5 Rich and Tracy (2010) and Boero et al (2014) discuss the problematic nature of fitting normal distributions to histograms where respondents place positive probability in less than three bins.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Our analysis relates to a number of recent empirical studies on the ECB-SPF data (e.g., Genre et al 2013;Kenny et al 2014Kenny et al , 2015Abel et al 2016;Glas and Hartmann 2016). Compared to these studies, the main innovation of the present paper is our use of ensemble methods for constructing forecast distributions.…”
mentioning
confidence: 99%
“…The European Central Bank's Survey of Professional Forecasters (ECB's SPF) is gaining prominence in recent years not only for policy analysis (ECB 2014a(ECB , 2014c but also for research (Lyziak and Paloviita 2016;Glas and Hartmann 2016;Kenny and Melo Fernandes 2016;Poncela and Senra 2016;Abel et al 2015;Bowles et al 2010;Conflitti 2011;Kenny et al 2012). The SPF was launched in the first quarter of 1999 and collects expectations of inflation, GDP growth and the unemployment rate in the euro area for different forecast horizons.…”
Section: Introductionmentioning
confidence: 99%
“…Abel et al (2015) found a strong negative relationship between uncertainty and aggregate real GDP growth forecasts. They did not use individual data in their analysis.…”
mentioning
confidence: 96%